Perspectives on the use of Grounded Theory in social development studies - Bumatay, Ernesto L. (2012)
This methodology paper introduces insights and perspectives on Grounded Theory (GT) as a social science research methodology. While GT estimates from the field of education, this paper shows that it can also be potentially used in development studies. The concept of the GT is first explained including the alternative views on its implementation. It has limited application in the Philippine context, and the current application that is cited is based on an education study called "Becoming Gift: A Classic Grounded Theory of Charism in Sectarian Institutions". The end goal of the paper is to argue for the application of GT in social development.
Keywords: Social sciences; Social development; Research methodology